IMPLEMENTASI KURIKULUM MERDEKA TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SMAN 1 SEBANGKI - Tilawati, Tilawati; Matsum, Junaidi H.; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study examines how the implementation of the Independent Curriculum influences students' learning motivation at SMAN 1 Sebangki. Using a qualitative case study approach, data were collected through interviews, observations, and documentation, involving nine informants: the principal, vice principal of curriculum, an economics teacher, and students. The findings indicate that since its implementation in the 2022/2024 academic year, the Independent Curriculum has positively impacted students"™ motivation. In intracurricular learning, economics classes have adopted teaching modules tailored to students' needs, supported by engaging and diverse learning media. Extracurricular activities, particularly scouting, have provided students with opportunities to develop their interests and talents outside the classroom. Additionally, the Pancasila Student Profile Strengthening Project (P5), with the theme Democratic Voice, has enhanced students' ability to think critically, communicate effectively, and collaborate. Furthermore, the school's culture promotes tolerance, fostering a safe and supportive learning environment. Despite these benefits, some students experience fluctuations in motivation due to mood changes, posing a challenge in maintaining consistent engagement. Nonetheless, the overall implementation of the Independent Curriculum at SMAN 1 Sebangki has contributed positively to students' enthusiasm for learning.